2010
DOI: 10.1111/j.1600-0722.2009.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Elution of substances from a silorane‐based dental composite

Abstract: Previous studies have shown that residual monomers, initiators, and additives are eluted from methacrylate-based dental composite materials. Recently, a composite material (Filtek Silorane), based on a new resin chemistry, was introduced. The purpose of this study was to investigate substances eluted from Filtek Silorane in water and ethanol. Polymerized specimen discs of the material were immersed in either distilled water or 75 vol% ethanol at 37 degrees C, and the solutions were analyzed using liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 10 publications
3
30
0
3
Order By: Relevance
“…However, when compared with methacrylate-based composite resins, similar mechanical properties [11,12] and a reduction in bacterial adhesion [13] were demonstrated. Some authors reported on higher flexural strength, fracture toughness [1], chromatic stability [14], the lack of cytotoxic effects [15], or no water solubility [16], but less compressive strength, microhardness [1], and translucency [14] were observed. Although a considerable amount of performance data are available, information for siloranebased materials on microleakage is limited.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, when compared with methacrylate-based composite resins, similar mechanical properties [11,12] and a reduction in bacterial adhesion [13] were demonstrated. Some authors reported on higher flexural strength, fracture toughness [1], chromatic stability [14], the lack of cytotoxic effects [15], or no water solubility [16], but less compressive strength, microhardness [1], and translucency [14] were observed. Although a considerable amount of performance data are available, information for siloranebased materials on microleakage is limited.…”
Section: Introductionmentioning
confidence: 97%
“…The material characteristics of composite resin restorations depend on various factors, such as amount and type of matrix resin [16], curing chemistry [17], initiator level [18], and the addition of non-bonded microfiller particles [19]. Due to 20-25% less filler content, inferior material properties (e.g., low fracture strength [20], less rigidity [21], and high polymerization shrinkage [22]) are observed for flowable composite resins than for conventional composite resins.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although several recent studies have evaluated physicochemical properties of silorane-based resins, [13][14][15][16][17] research on their biologic effects is quite limited, being based mostly on in vitro and cell culture studies. 5,10,18 To the best of our knowledge, the in vivo pulpal and periapical response to these new restorative systems has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…With time, the composition of the restorative materials changes due to chemical and mechanical degradation in the oral cavity. They may also influence the health of oral soft tissues in several ways especially by delivering water soluble components [1][2][3] into saliva/oral cavity as well as by interacting directly with adjacent tissues like epithelia of gingiva and its connective tissue [2]. It has been shown that, the organic matrix of the dental composite resins, when released into the oral cavity can cause a wide variety of adverse biological reactions such as mucosal irritation, epithelial proliferation, oral lichenoid reaction, hypersensitivity, anaphylactoid reactions and may also cause fibrosis of the adjacent soft tissue [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%